KCNA4 gene variant is auxiliary in endurance running performance level - Flecha-Velazquez, K.; Fahey, T. D.; Martinez, J. L.; Lopez-Taylor, J. R.; Rivera, M. A. (International Journal of Sports Medicine, 2019)
The present is an observational study following a genetic epidemiology model using a case-control design. We tested the hypothesis of an association between the prevalence of the genotypic and allelic frequencies distribution of the potassium voltage-gated channel of the shaker related subfamily member 4 gene (KCNA4) rs1323860 (C/T transition) and endurance performance level in Hispanic male marathon runners (MR). The subjects (n=1876) were adult Hispanic male MR. Fast-MR (cases; n=938) were finishers in the top 3rd percentile. Slow MR (controls; n=938) were finishers in the lowest 3rd percentile of their respective age. Genomic DNA was purified from a whole blood sample. Polymerase chain reaction was used to amplify a KCNA4 SNP which consists of a C/T (rs1323860) transition. The observed genotype frequencies, in both Cases and Controls, met Hardy-Weinberg equilibrium (X2, P=0.05). Genotype and allele frequencies were statistically different (P<0.01) between cases and controls. Odds ratio revealed that the C allele was 1.33 times more likely prevalent in the cases than in the controls (95% CI; 1.17, 1.51; P<0.001). The magnitude of the statistical power for the present study was 0.86. In conclusion, the findings strongly suggest that KCNA4 gene rs1323860 (C/T transition) is auxiliary in the complex phenotype of endurance running performance level in Hispanic male marathon runners.